(untitled) (Revista de História Regional, 2023)
This article narrates and discusses the process of proposing and approving the Statute of Civil Public Employees of the State of Paraná, based on the actions guided mainly by the executive and the legislature between the years 1947 and 1950. Therefore, starting from the establishment of some elements that composed the existing conditions in Paraná in terms of meeting the demands of the population by the State, it is discussed how the government actions were articulated to those demands while building the state public service.